If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -77 = 0 Reorder the terms: -77 + 11x = 0 Solving -77 + 11x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '77' to each side of the equation. -77 + 77 + 11x = 0 + 77 Combine like terms: -77 + 77 = 0 0 + 11x = 0 + 77 11x = 0 + 77 Combine like terms: 0 + 77 = 77 11x = 77 Divide each side by '11'. x = 7 Simplifying x = 7
| 3x^2-25x+42=0 | | 275m^2+396n^2=0 | | 4y+112=180 | | x^2-x-48=16 | | 0.5(x-0.08)=0 | | x/3=3x-1 | | ln(x)+ln(8x)=-3 | | 5y+20=0 | | 5b+7b=60 | | s^2-12s+36= | | (x-2)/3=8 | | (x-2)/3-5=3 | | 4x^3+12x^2+10x+10=0 | | x-2/3-5=3 | | 2x+30+x= | | 24=-8(0.3p+9) | | 4(3x-2)=(6x+6) | | 4X+37+9X=180 | | X=45(16) | | 29x^2-7x=0 | | 0.50x+0.45(90)=0.25(124) | | 5x+8-12=-6x-2x+3 | | -4x-6+x=-2x+6-10 | | 0(n)=2n-1 | | -8(v+4)+2v+6=7v+9 | | (x+7)(x+6)= | | 4x+11=77x-7 | | 3x+15=3x+3 | | 3x^2-6=4x | | 6x(5x+7)= | | x^2+7x-13=2x | | 110-9x=10x+23 |